Monitoring lung recruitability during recruitment maneuvers in children with respiratory failure on ECMO using electrical impedance tomography: case report - Clausen, Jan-Christoph; Krauß, Annemarie; Schulz, Antonia; Miera, Oliver (Frontiers in Pediatrics, 2025)
IntroductionCurrently, there are no clear guidelines regarding the use of recruitment maneuvers in pediatric patients with severe respiratory failure who are on extracorporeal membrane oxygenation (ECMO), nor is there consensus on how they should be performed.MethodsIn this report, we describe pulmonary recruitment maneuvers performed in four children with respiratory failure on ECMO (three on VA-ECMO and one on VV-ECMO), all of whom were monitored using electrical impedance tomography (EIT) between March and December 2024.ResultsOur findings demonstrate that EIT is a feasible tool for evaluating lung recruitability in children with severe respiratory failure on ECMO. Additionally, EIT aids in distinguishing between responders and non-responders to recruitment maneuvers.